Cognitive Impairment and the correlation with genetic Expression of GAD67, Gad65 and GABA beta2 Using Human Induced Pluripotent Stem Cells - D. Khalifa; H. Gabr; H. Fathy; H. Abdou; M. Batrawy (European Psychiatry, 2022)
Introduction Alteration of GABergic neurotransmission is accused to be sharing in the cognitive impairment in schizophrenia. Exploring the relation between the neuronal expression of GABergic genes and cognitive impairment in living patients through modeling of schizophrenia is an important step to know more about the core of the pathophysiology of this disorder